RESPONSE OF NEW LATE BLIGHT RESISTANT CULTIVARS OF POTATO (SOLANUM TUBEROSUM) TO DIFFERENT LEVELS OF FERTILIZERS IN HIGH HILLS OF NORTH-WESTERN HIMALAYA - Sharma, Ashwani Kumar (Potato Journal, 2017)
Field experiments were conducted to evaluate the performance of two late blight resistant potato cultivars Kufri Girdhari and Kufri Himalini under high hills of north-western Himalaya at different fertility levels. Results indicated that both the cultivars were found to be similar for the majority of the parameters except for haulms weight per plant and potato yields. However, varying levels of fertility had a significant influence on per cent ground cover, plant height, number of shoots, compound leaves and haulms weight per plant as well as on the potato yields. Number of tubers per hectare did not vary significantly between the cultivars as well as with the doses of fertilizers. A dose of 125% NPK (150: 125:125 kg/ha) was found optimum for realizing maximum yields in Kufri Himalini, whereas, 100% NPK (120:100:100 kg/ha) was found optimum for Kufri Girdhari with crop duration of 120 days. Kufri Himalini tended to produce higher proportions of large size tubers than Kufri Girdhari.